Exploring the use of ChatGPT as a virtual health coach for chronic disease management - Fahad M. Al‐Anezi (Wiley, 2024)
Abstract Introduction ChatGPT has been widely researched for its potential in gealthcare applications. However, its efficcy as a virtual health coach is one of the important areas, which can significantly contribute to the sustainablility in healthcare operations, especially in managing critical illnesses. Therefore, this study aims to analyze the use of ChatGPT as a virtual health coach for chronic disease managemet. Methods This study used a quasi‐experimental design because ChatGPT is a relatively new technology and few people have experience with it. Patients who were receiving care outside of the hospital were included. Semi‐structured interviews were conducted after a 2‐week period in which participants used ChatGPT to search for health information about chronic disease management. Thirty‐nine outpatients were interviewed and thematic analysis was used to analyze the interview data. Results The findings suggested both opportunities and challenges of using ChatGPT as a virtual health coach for chronic disease management. The major opportunities identified included life‐long learning, improved health literacy, cost‐effectiveness, behavioral change support, scalability, and accessibility. The major challenges identified included limited physical examination, lack of human connection, legal and ethical complications, and lack of accuracy and reliability. Conclusion ChatGPT‐based technologies may serve as a supplementary or intermediate support system. However, such applications for managing chronic diseases must protect privacy and promote both short‐ and long‐term positive outcomes.